ANALISIS PENERAPAN PSAK SYARIAH PADA KOPERASI SYARIAH BMT ARMA DI PALEMBANG - Husniyyatun, Lidiya Amiroh; Abel, Avianda Bareta; Fransiska, Mauliddiah Charla; Cahaya Azwari, Peny (EKSYDA: Jurnal Studi Ekonomi Syariah, 2025)
This study aims to analyze the implementation of the Islamic Financial Accounting Standards (PSAK) at BMT Arma, a Sharia cooperative based in Palembang. The focus is on evaluating the application of PSAK 102 (Murabahah), PSAK 105 (Mudharabah), and PSAK 107 (Ijarah), to determine the extent to which BMT Arma's financial practices align with Sharia principles and the standards issued by the Sharia Accounting Standards Board (DSAS). Data were collected through in- depth interviews with management and staff, as well as a review of financial reports and financing contracts. The findings reveal that BMT Arma has successfully implemented PSAK 102 and PSAK 107, particularly in the recording and reporting of murabahah and ijarah transactions. Murabahah is applied using a wakalah contract scheme, while ijarah is used to finance services such as education, healthcare, and trade. However, the implementation of PSAK 105 remains unclear, especially in terms of investment recognition and profit-sharing mechanisms. These findings highlight the need to strengthen the accounting competencies of human resources through adequate training. Overall, BMT Arma demonstrates a strong commitment to Sharia compliance, which plays a critical role in building public trust and institutional accountability.